Determining the Synthesis and Characterization of Some Novel Meso Functionalized Unsymmetrical Metalloporphyrins - Gujarathi, Pradip B. (Challenges and Advances in Chemical Science Vol. 5, 2021)
In this article, we describe the synthesis of meso substituted tetraaryl unsymmetrical metalloporphyrins (A3B). Two common methods used for metalation of porphyrins are the acetate method and dimethyl formamide method. By reacting unsymmetrical porphyrins with metal acetates, new porphyrins with different functionalizations at the meso-position (A3B type) and their cobalt, nickel, copper, and zinc complexes were synthesised. UV, IR, NMR, and mass spectra were used to characterise the metalloporphyrins that were synthesised. ESR spectra and magnetic measurements for complexes(1a, 1c and 3c) were used to further investigate the copper complexes 1c and 3c. Similarly, fluorescence spectra were used to study the zinc complexes of 1d and 3d.